COMPARATIVE ANALYSIS OF THE RESULTS OF AGROCHEMICAL MONITORING OF SOIL UNDER MULTI-ANNUAL PLANTINGS (CULTIVATION USING ORGANIC TECHNOLOGY) AND MULTI-ANNUAL HERBS (CULTIVATION USING TRADITIONAL PESTICIDE-FREE TECHNOLOGY) - Ласло, Оксана; Марініч, Любов (SWorldJournal, 2025)
Soil monitoring is an important tool for obtaining up-to-date information about their condition, which allows predicting changes in soil cover and planning effective measures to prevent its degradation. Scientists emphasize that today the issue of environ